2014
DOI: 10.4012/dmj.2013-306
|View full text |Cite
|
Sign up to set email alerts
|

Influence of post and core materials on distortion around 4-unit zirconia bridge margins

Abstract: The purpose of this study was to evaluate the surface strain of zirconia fixed partial denture frameworks and their abutment roots when restored with two types of post and core materials. Artificial mandibular first premolars and second molars were used as the abutment teeth. Posts and cores were of two types: resin composite with glass fiber posts (RC) and cast platinum gold alloy (MC). The cores and 4-unit zirconia frameworks were bonded to the specimens. Static loading was applied to the occlusal surfaces, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Zirconia has garnered much attention as a restoration material. Zirconia is needed because it has superior biocompatibility compared to metal and has better aesthetics than a metal frame [6][7][8][9] . A clinical problem with this technique is the chipping of, and damage inflicted upon, the porcelain facing the zirconia crown due to occlusal force.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia has garnered much attention as a restoration material. Zirconia is needed because it has superior biocompatibility compared to metal and has better aesthetics than a metal frame [6][7][8][9] . A clinical problem with this technique is the chipping of, and damage inflicted upon, the porcelain facing the zirconia crown due to occlusal force.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some studies 17,18) have reported that the Young's modulus of the zirconia framework is greater than that of metal framework, which may help in preventing the fracture of the porcelain veneer. However, few studies 21) have evaluated both post and core materials and framework materials. The difference in the Young's modulus between the abutment teeth and the FPD framework on stress distribution has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study led by Inagaki et al 21) investigated the surface strain of zirconia FPD frameworks and the roots of the abutment teeth when the missing posterior teeth were replaced by a 4-unit Y-TZP framework, and when the abutment teeth were additionally restored with two types of post and core materials. The study reported that high surface strain was detected, particularly at the premolar abutment, and that the cast post and core system played a role in limiting the magnitude of surface strain on the framework.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations